“Fuldtud korrekt og værdig Optræden”. Politik, social kontrol og offentlighed under besættelsen af Danmark 1940-45“ - Olesen, Niels Wium (Passage - Tidsskrift for litteratur og kritik, 2011)
Niels Wium Olesen: “‘Completely Correct and Dignified Behaviour’: Politics, Social Control and the Public Sphere During the Occupation of Denmark 1940-45” In order to secure the survival of the Danish state and society during the Second World War, extensive social control was exercised by the Danish government, the political parties and the civil society. The social control supported national unity and set the limits of what was acceptable and unacceptable behaviour in the public sphere.